Comparison of Clinical Outcomes Between Ticagrelor and Clopidogrel in Acute Coronary Syndrome: A Comprehensive Meta-Analysis - Sun, Mengyi; Cui, Weichen; Li, Linping (Frontiers in Cardiovascular Medicine, 2022)
Background: Ticagrelor is currently recommended for patients with acute coronary syndrome (ACS). However, recent studies have yielded controversial results. Objective: To compare the clinical outcomes between ticagrelor and clopidogrel in ACS patients. Methods: Three electronic databases were queried until April 25, 2021. We defined major adverse cardiovascular event (MACE) as the primary efficacy endpoint. The secondary efficacy endpoints included stroke, stent thrombosis (ST), cardiovascular (CV) death, all-cause death, and myocardial infarction (MI). The safety endpoints were (major and minor) bleeding. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to represent the estimated effect sizes. Results: A total of 270,937 ACS patients from 10 clinical trials and 18 observational studies were included. No significant difference was detected in MACE (OR 0.81, 95% CI 0.60-1.08, p = 0.15, I² = 64.83%). However, ticagrelor introduced a higher risk of bleeding (1.46, 1.17-1.83, 0.00, 61.66%) and minor bleeding (1.71, 1.33-2.21, 0.00, 4.65%) in clinical trials. The results of secondary efficacy endpoints differed in the clinical trials and observational studies. Subgroup analysis demonstrated that ticagrelor showed better therapeutic effects in patients underwent percutaneous coronary intervention (PCI) (0.38, 0.23-0.63, 0.00, 0) than those intended for PCI (1.03, 0.76-1.38, 0.87, 64.26%). Meanwhile, ticagrelor showed different therapeutic effects on ACS patients of different ethnicities and different countries. Conclusion: This meta-analysis demonstrated that ticagrelor is not superior to clopidogrel in MACE but is associated with a higher risk of bleeding in ACS patients. Different PCI strategies, ethnicities, and countries may be the factors that contribute to different therapeutic effects of ticagrelor.